Copper electrodeposition on glassy carbon and highly oriented pyrolytic graphite substrates from perchlorate solutions - Diana Elizabeth García-Rodríguez; Luis Humberto Mendoza-Huizar; Clara Hilda Rios-Reyes; Martín Alejandro Alatorre-Ordaz (Química Nova, 2012)
In present work, we analyzed the copper electrodeposition onto GCE (System I) and HOPGE (System II) from perchlorate solutions. The current density transients obtained from system I and II were well described through a kinetic mechanism that involves four different contributions: (a) a Langmuir type adsorption process, b) an electron transfer from Cu2+→Cu+, (c) a 3D nucleation limited by a mass transfer reaction and (d) a proton reduction process. It was observed that the values of the nucleation rate, the number of active nucleation sites were increased with the overpotential and they are bigger onto GCE in comparison with HOPGE.